Thermophysical Properties of Light and Heavy Water from Second Virial Coefficient; Isotopic Substitution Effect - M. Najafi; S. Ammari Allahyari (Journal of Nuclear Research and Applications, 2024)
In this paper, some thermophysical properties of light and heavy water will be predicted and modeled using the virial equation of state (VEOS), and the effect of isotopic substitution will be studied. In this respect, by fitting the experimental and theoretical data of the second virial coefficient of light and heavy water in the temperature range of 300 to 1800 K, a new equation will be presented, using which the thermodynamic properties of the aforementioned fluids will be predicted and . The results are compared with the experimental data to evaluate the model and the new equation of the second virial coefficient. The results show that this approach has a very good ability to predict the thermophysical properties of light and heavy water. It will also demonstrate that deuterium isotopic substitution reduces the attractive interaction between molecules, especially above the critical temperature, and this causes the difference in the thermodynamic properties of the two fluids. The calculations performed in the above temperatures and pressure range using viral coefficients to determine thermophysical properties of light and heavy water and also the investigation of the effect of isotopic substitution are novelties of this article.